Factors affecting foreign direct investment in Malaysia: a Bayesian model averaging approach - Tiong, Kui Ming (2022)
In the past, FDI studies were developed mainly based on Dunning‘s Ownership-Location-Internalisation paradigm. However, digitalisation has brought the importance of information and communications technology, while globalisation has brought the importance of political and social institutions in facilitating investment. In addition to location-specific advantages which focus on macroeconomic factors, digitalisation and institutional factors should be considered to explain FDI. Hence, this study identified key factors affecting FDI in Malaysia by taking into consideration the current development of digitalisation and globalisation. In the presence of many potential FDI factors, the Bayesian Model Averaging (BMA) approach was selected to overcome the uncertainty in variable selections. At the country-level study, the Information and Communications Technology-Economic-Institutional, ICT-E-I model was developed. Based on a panel of 32 economies for the period 2010 to 2017, the BMA findings show that Logistics Index (PIP = 1.00) and Bilateral Trade (PIP = 1.00) have a very strong effect on FDI, while Governance Index (PIP = 0.93), Cultural Distance (PIP = 0.85), Geographic Distance (PIP = 0.78) and ICT Telecommunication Infrastructure (PIP = 0.76) have a moderate effect on FDI. Besides, at the firm-level study, based on the Enterprise Surveys 2015 of 692 firms, the BMA findings show that access to land (PIP = 1.00) and crime, theft, and disorders (PIP = 1.00) have a very strong effect on FDI. The BMA approach highlights the relative importance of institutional factors in explaining FDI. Hence, improving the investment climate relies more on the soft and hard ―infrastructure‖. Soft infrastructure refers to a conducive institutional environment for investment, while hard infrastructure refers to the ICT telecommunication and transport infrastructure. The finding signifies a shift in the importance of FDI factors from an economic to an institutional lens.